Muscle endurance: Is bipedalism the cause? - D’Antona, Giuseppe; Burtscher, Martin (Frontiers in Ecology and Evolution, 2022)
One may ask if the transition to bipedalism from the condition of quadrupedalism, which occurred about 7 million years ago, has been the cause or consequence of a series of fundamental physiological muscular aspects including the cost of locomotion, a crucial determinant of endurance, which has been found to be significantly lower in humans than in apes. This issue strictly links to unsolved issues regarding the significance of several muscular structural and functional adaptations, classically attributed to bipedalism and its associated locomotions, which we cannot simply attribute to the acquisition of the upright position and which may directly or indirectly contribute to the observed changes in muscle energetics that make the modern human an exceptional endurance walker and runner compared to quadrupedals.